Effect of direct fed microbials on nutrient utilization, rumen fermentation, immune and growth response in crossbred cattle calves - CHAUDHARY, L C; SAHOO, A; AGARWAL, NEETA; KAMRA, D N; PATHAK, N N (The Indian Journal of Animal Sciences, 2011)
The study was conducted to test efficacy of direct fed microbials (DFM) for the improvement of performance of crossbred cattle calves reared on the diet devoid of cereal grains. Day-old calves (32) with average body weight of 23 kg, were divided into 4 groups and fed on concentrate mixture to meet 50% dry matter requirement and green fodder ad lib. Group 1 served as control. The 100 ml DFM culture was fed to group 2 (curd, 108 cfulml), group 3 (Saccharomyces cerevisiae 49,106 cfulml) and group 4 (Lactobacillus acidophilus 15,108 cfu/ml). The experiment lasted 52 weeks. The dry matter intake and feed conversion efficiency "Yere not affected due to supplementation of any of the DFM. Improved body weight gain in calves by supplementation of all the 3 microbial additives was observed. The digestibility of nutrients and plane of nutrition were similar in all the 4 groups at 14 weeks and 52 weeks except a significant increase in the digestibility of ether extract and acid detergent fibres in S. cerevisae fed group at 14 weeks and 52 weeks, respectively. There was no difference among the groups in the levels of lactic acid, NH3-N, total and molar proportion of volatile fatty acids, ciliate protozoa count and activities of filter paper degrading enzyme, caroxymethylcellulase, xylanase, a ..amylase, ~-xylosidase, ~-glucosidase, a.-glucosidase and protease at 52 weeks of age. However, microcrystalline cellulase activity was significantly higher in L. acidophilus fed group. The blood biochemical characteristics (plasma glucose, serum protein, albumin and globulin) and immunological status of the calves of all the groups were similar at 52 weeks of age. It is concluded from the study that long tenn (from birth to one year of age) feeding of DFM improved the growth perfonnance of crossbred cattle calves fed diet devoid of cereal grains.Â